2014
DOI: 10.1093/nar/gku1151
|View full text |Cite
|
Sign up to set email alerts
|

MethHC: a database of DNA methylation and gene expression in human cancer

Abstract: We present MethHC (http://MethHC.mbc.nctu.edu.tw), a database comprising a systematic integration of a large collection of DNA methylation data and mRNA/microRNA expression profiles in human cancer. DNA methylation is an important epigenetic regulator of gene transcription, and genes with high levels of DNA methylation in their promoter regions are transcriptionally silent. Increasing numbers of DNA methylation and mRNA/microRNA expression profiles are being published in different public repositories. These da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
217
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(226 citation statements)
references
References 29 publications
8
217
0
1
Order By: Relevance
“…We examined DNA methylation of the HEXIM1 locus using MethHC (Huang et al, 2015) to analyze melanoma methylation data from The Cancer Genome Atlas (TCGA). The HEXIM1 promoter is hypermethylated in tumor samples, suggesting that hypermethylation downregulates HEXIM1 (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…We examined DNA methylation of the HEXIM1 locus using MethHC (Huang et al, 2015) to analyze melanoma methylation data from The Cancer Genome Atlas (TCGA). The HEXIM1 promoter is hypermethylated in tumor samples, suggesting that hypermethylation downregulates HEXIM1 (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…The tumor-suppressor function of EphB1 in AML and the association in a variety of cancers between loss of expression and aggressive tumor phenotypes implies that EphB1 is an important regulator of common cancer cell–transforming pathways (12, 13, 34). Conformingly, we used the MethHC DNA methylation database in human cancers (35) to analyze EphB1 promoter CpG site methylation and found common promoter hypermethylation enriched at the 5′ untranslated regions (Supplementary Fig. S3, all cancers P < 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…Although single CpG methylation patterns might be a potential biomarker for cancer risk assessment [35], it has also been suggested that different genomic regions can be associated with differential survival prognosis [36]. Moreover, several recently published web tools emphasize the need for analyzing DNA methylation data based on sub-regions [9,10]. Therefore, we provide the users with a detailed overview of individual CpG sites with the options to select genomic regions (relative to CGI and gene sub-region), methods to establish cut-off points for dichotomizing higher and lower methylation patient groups (mean, median, lower quantile, upper quantile and maxstat) and adjustment type.…”
Section: Construction Of the Web Toolmentioning
confidence: 99%
“…However, analyzing the raw data from such consortia is a labor-intensive and time-consuming process that requires specific bioinformatics skills. Multiple public resources such as Wanderer [9], METHHC [10] and MEXPRESS [11] provide a simple user interface to explore the relationship between methylation and gene expression data originating from TCGA. Additionally, tools to perform survival analysis using gene expression data from TCGA are also available to the research community [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%